2022
DOI: 10.3389/fphar.2022.887253
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification: New Insights Into BMP Type I Receptor A

Abstract: Vascular calcification (VC) is a complex ectopic calcification process and an important indicator of increased risk for diabetes, atherosclerosis, chronic kidney disease, and other diseases. Therefore, clarifying the pathogenesis of VC is of great clinical significance. Numerous studies have shown that the onset and progression of VC are similar to bone formation. Members of the bone morphogenetic protein (BMP) family of proteins are considered key molecules in the progression of vascular calcification. BMP ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Eosinophils or mEar1/ECP/EDN increased SMC expression of ALP, a known enzyme involved in SMC calcification. 66 The expression or functions of transcription factor osterix and transcription repressor msh homeobox-2 are also downstream targets of p-Smad-1/5/8 activation, 67 which eosinophils and mEar1/ECP/EDN may regulate.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils or mEar1/ECP/EDN increased SMC expression of ALP, a known enzyme involved in SMC calcification. 66 The expression or functions of transcription factor osterix and transcription repressor msh homeobox-2 are also downstream targets of p-Smad-1/5/8 activation, 67 which eosinophils and mEar1/ECP/EDN may regulate.…”
Section: Discussionmentioning
confidence: 99%
“…The Involvement of SMAD signaling pathways via TGF family receptors in smooth muscle cell calcification has been extensively studied in the past [43,44]. While SMAD1/5/8 is classically activated via BMP2 in VSMC and leads to vascular calcification [44][45][46], SMAD2/3 has been directly linked to TGFβ activation and promotes smooth muscle cell differentiation [47,48]. Interestingly, we showed that LRG1 enhanced the activation of the TGFβ-induced SMAD1/5 signaling pathway in VSMC without affecting the SMAD2/3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are members of the TGF-β superfamily essential for development, but they also participate in the regulation of cardiovascular structure and function. The extracellular binding of BMP to type I and type II receptors leads to the formation of heteromeric signaling complexes [ 99 , 100 ]. The canonical pathway induces the phosphorylation of Smad1/5/8 (R-Smad), which binds to Smad4 and the complex translocates into the nucleus to regulate gene expression [ 101 ].…”
Section: Molecular Networking In Vascular Calcificationmentioning
confidence: 99%